Power, Identity and Subtitling in a Diglossic Society - Yau, Wai-Ping (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This article attempts to address the problematics of identity and power relations as they arise in the practice of subtitling. Specifically, the article asks questions about how subtitling can play an active part in the shaping of identity by mediating between the local, the national and the global, and how the subtitler can be an agent in adjusting the power relations between cultural constituencies. These questions are considered in the context of a diglossic society, not only because issues about language, identity and power relations are inextricably involved in discussions about diglossia, but also because diglossia is a common experience for many subtitlers and film audiences. The possibility is explored that the subtitler can create a hybrid language that redefines the rigid roles assigned to the local dialect and the national language and revises our codes for reading subtitles. Examples from Hong Kong are used to illustrate these points.